Hakikat Pendidikan dan Karir Perempuan dalam Perspektif Hukum Islam - Raodahtul Jannah (AN-NISA, 2019)
The Essence of Women's Education and Career in the Perspective of Islamic Law This paper examines the nature of women's education and careers in the perspective of Islamic law through the literature review method. In Islamic view, women have the same position as men in terms of education and teaching. Seeing one position of women in Islam that is as a mother, then education for women is very important for the interests and future of this nation itself. It can be said that intelligent mothers will grow smart offspring as well. Protection of women's education provided by Islam, provides opportunities for women to develop their careers in accordance with their interests. This is because a career is a job that requires education. Although career women are allowed in Islam, they must always prioritize the aspects of goodness and benefits for the household and society. If there is more detrimental harm to the family then work outside the home must be abandoned. So in essence women are allowed to work outside the home as long as the work does not violate Islamic Sharia principles. Abstrak Artikel ini membahas sifat pendidikan dan karir perempuan dalam perspektif hukum Islam melalui metode tinjauan literatur. Dalam pandangan Islam, wanita memiliki posisi yang sama dengan pria dalam hal pendidikan dan pengajaran. Melihat satu posisi wanita dalam Islam yaitu sebagai seorang ibu, maka pendidikan bagi wanita sangat penting untuk kepentingan dan masa depan bangsa ini sendiri. Dapat dikatakan bahwa ibu yang cerdas akan menumbuhkan anak yang pintar juga. Perlindungan pendidikan perempuan yang diberikan oleh Islam, memberikan peluang bagi perempuan untuk mengembangkan karier mereka sesuai dengan minat mereka. Ini karena karier adalah pekerjaan yang membutuhkan pendidikan. Meskipun wanita karier diperbolehkan dalam Islam, mereka harus selalu memprioritaskan aspek kebaikan dan manfaat bagi rumah tangga dan masyarakat. Jika ada lebih banyak kerusakan yang merugikan bagi keluarga maka pekerjaan di luar rumah harus ditinggalkan. Jadi intinya perempuan diizinkan bekerja di luar rumah selama pekerjaan itu tidak melanggar prinsip syariah Islam.